Navigating hardships: socio-economic struggles of single mothers in informal trade amidst the Covid-19 pandemic: a Mabvuku community case study - Leon Marongedza; Promise Machingo Hlungwani; Precious Hove (Cogent Business & Management, 2024)
This study evaluates the lived experiences of single mothers involved in informal trading in the high density suburb of Mabvuku at the height of Covid-19 induced lockdowns. Using a mixed methodology with a slant towards qualitative enquiry, the study employed focus group discussions, document analysis as well as a questionnaire. Researchers studied the environment in its natural settings and interpreted phenomena in terms of the meaning single mothers expressed in the study. An interpretive philosophy was the main anchor to the study; hence purposive sampling was used to select single mothers involved in informal trade as participants. The main objectives of the study were to determine the resilience of single mother informal traders during the Covid-19 era; analyse the socio-economic challenges faced by the single mothers in informal trade during the Covid-19 era and to explore the intervention strategies available to address challenges faced by unemployed single mothers in the Covid-19 context. Findings were analysed qualitatively through data reduction and conclusion drawing where verification of irregularities, patterns, explanations and propositions were emphasised. Quantitative aspects elicited through a questionnaire distributed to hundred single mothers were presented in tables enriched by descriptive narratives. The questionnaire profiled the demographic characteristics of respondents and type of business operated by the single mothers in the study. Overall, the study foregrounds that the introduction of lockdown restrictive measures dealt a major blow to the single mothers trading enterprises leaving most of them out of business. Whilst there were some elements of resilience and recovery, the majority of single mothers failed to cope with the strenuous environment under Covid-19.
Keywords: 650; Informal trade; single mothers; socio-economic challenges; Covid 19